Organic and inorganic fertilization on the yield and quality of soybean (Journal of the Bangladesh Agricultural University, 2014)
Combined application of organic and inorganic fertilizers can play an important role for increasing yield and quality of soybean. Therefore, a field experiment was conducted at Genetics and Plant Breeding farm, Bangladesh Agricultural University from July to November, 2011 to evaluate the effect of cowdung and poultry manure with chemical fertilizer on the yield and quality of soybean cv. BINA soybean-2. The experiment was laid out in randomized complete block design having 9 treatments viz. control (CT), 100% recommended dose of chemical fertilizers (RDCF100%), 50% RDCF (RDCF50%), cowdung 10 t ha-1 (CD10 t ha-1), 50% RDCF + CD 5 t ha-1 (RDCF50% + CD5 t ha-1), 75% RDCF + CD 3 t ha-1 (RDCF75% + CD3 t ha-1), poultry manure 3 t ha-1 (PM3 t ha-1), 50% RDCF + PM 1.5 t ha-1 (RDCF50% + PM1.5 t ha-1) and 75% RDCF + PM 1 t ha-1 (RDCF75% + PM1 t ha-1) with 3 replications. All the treatments significantly influenced the yield, yield attributing parameters and protein content except oil content of BINA soybean-2. The highest plant height, yield, branches plant-1, filled pods plant-1, grain plant-1 and 100-grain wt. were found in RDCF100%, which were statistically identical with RDCF75%+PM1 t ha-1 and RDCF75%+CD3 t ha-1 and the lowest values of all the parameters were obtained from control treatment. The maximum protein content was observed in RDCF100%, which was identical to RDCF75%+PM1 t ha-1 and RDCF75%+CD3 t ha-1 and the lowest value was found in control. The overall finding of this study indicated that organic manure in combination with the recommended dose of chemical fertilizers can be applied to achieve better yield and quality of soybean as well as to improve soil fertility status. DOI: http://dx.doi.org/10.3329/jbau.v11i1.18199 J. Bangladesh Agril. Univ. 11(1): 23-28, 2013